Scoping review: teoretický rámec a metodologické poznámky - Chrastina, Jan (Ošetrovateľstvo, 2019)
Background: Scoping reviews (ScoRev) have a dominant position in nursing and healthcare research. Both ScoRev and systematic review (SysRev) have methodological frameworks that have both common and different processing steps. Since ScoRev is considered to be a precursor for SysRev, both types need to be viewed by the researcher's synchronous optics and understand the requirements for these types of work. Aim: To define and describe the methodological framework of scoping review processing and point out the matches and differences in scoping review and systematic review. Results: The paper described the framework for processing ScoRev and defining the basic differences between ScoRev and SysRev. ScoRev and SysRev processing procedures are described in detail – terminological chaos, however, appears in the titles of published ScoRev studies, either confusing with SysRev or incorrectly combining these two separate types of review approaches. Conclusion: in nursing research, in the context of ScoRev, it is necessary to maintain the terminological clarity and precision for ScoRev processing. As a suitable format for the ScoRev titles is recommended "Specific title, description of the phenomenon studied and definition of relationship/purpose, benefit: scoping review".
Keywords: Publishing; lidé; publikování; Terminology as Topic; Humans; terminologie jako téma